Effects of drying methods on oxidative stability of roselle seed oil (Hibiscus Sabdariffa): an optimization approach - Jahurul, M. H. A.; Shian, O. K.; Sharifudin, M. S.; Hasmadi, M.; Lee, J. S.; Mansoor, A. H.; Jumardi, R.; Firoz Khan, M.; Jinap, S.; Mohd Omar, A. K.; Sarker, Md. Zaidul Islam (Springer Nature, 2020)
The objective of this study was to optimize the extraction of oil from pre-dried roselle seeds using response surface methodology (RSM). We also determined the oxidative stability of oil extracted from oven and freeze-dried roselle seed in terms of iodine value (IV), free fatty acid (FFA) value, peroxide value (PV), P-anisidine and total oxidation values (TOTOX value). The RSM was designated based on the central composite design with the usage of three optimum parameters ranged from 8 to 16 g of sample weight, 250–350 mL of solvent volume, and 6–8 h of extraction time. The highest oil yielded from roselle seed using the optimization process was 22.11% with the parameters at sample weight of 14.4 g, solvent volume of 329.70 mL, and extraction time of 7.6 h. Besides, the oil extracted from the oven dried roselle seed had the values of 89.04, 2.11, 4.13, 3.76 and 12.03 for IV, FFA, PV, P-anisidine, and TOTOX values, respectively. While for the oil extracted from freeze-dried roselle seed showed IV of 90.31, FFA of 1.64, PV of 2.47, P-anisidine value of 3.48, and TOTOX value of 8.42. PV and TOTOX values showed significant differences whereas; IV, FFA, and P-anisidine values showed no significant differences between the oven and freeze-dried roselle seed oils.